The Neutrality Crisis Of The State Civil Apparatus: Practical Politics Unethic Public Bureaucrats (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2022)
This study aims to analyze the State Civil Apparatus (SCA) neutrality violations and various efforts to reduce it neutrality. A qualitative descriptive method was used and data was collected through a literature study that reviewed cases in 2020. The results showed that the neutrality violations later became a problem that causes discontinuity and disharmony within the SCA. Commonly, the violation form is encountered through indirect campaigns on social media. The SCA neutrality violations are mostly caused due to the motive of getting a higher position. In conclusion, the government establishes the State Civil Apparatus Commission (SCAC) and the merit system to solve the SCA problem